Análisis de la memoria gráfica de la explosión del polvorín año 2002 - Eduardo Javier, Ramos Chávez (2020)
The research "Analysis of the graphic memory in Riobamba powder keg in 2002 aimed to demonstrate if the image contents published in the local printed media, Diaro Los Andes and La Prensa newspaper from November 22 to December 30, 2002, accomplished the basic requirements for developing a photograph. An analysis card was used to check the fundamental requirements for taking a photographic image. The three levels of image analysis were taken into account, which were morphological, compositional, and enunciative